Conjugated diene polymer composition
By designing a conjugated diene polymer composition, adjusting the glass transition temperature and controlling the difference between iodine price and SP value, the problem of balance between tire wear resistance and braking performance in the prior art is solved, and rubber is realized High performance and excellent damage resistance of the compound.
Patent Information
- Application Number
- CN202110893837.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-08-07
- Filing Date
- 2021-08-04
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2041-08-04
AI Technical Summary
In the prior art, when improving tire wear resistance, it is difficult to simultaneously optimize the tire's glass transition temperature and compatibility with other polymers, resulting in poor balance of braking performance and wetland grip performance.
By designing a composition containing a conjugated diene-based polymer (A) and a conjugated diene-based polymer (B), the glass transition temperature is adjusted, and by controlling the difference between iodine valence and SP value, the mixing is improved degrees of freedom to optimize the performance of rubber compound.
The balance between the fuel-saving performance of the rubber compound after vulcanization and the wetland grip performance is achieved, and the damage characteristics and breaking strength changes after heating are improved.
Smart Images

Figure BDA0003195627490000291 
Figure BDA0003195627490000301 
Figure BDA0003195627490000321
Abstract
Description
Technical Field
[0001] The present invention relates to a conjugated diene polymer composition. Background Art
[0002] As autonomous driving technology becomes more prevalent in the future, there is a demand to reduce the frequency of tire replacement, that is, to improve tire durability. In particular, regarding braking performance, it is required to maintain performance for a longer period than before in order to ensure the safety of passengers.
[0003] In order to improve the durability of tires, it is essential to improve the wear resistance of tires. For example, Patent Document 1 discloses a technology for improving the wear resistance by using a hydrogenated conjugated diene rubber containing an ethylene structure in a tire tread.
[0004] In addition, it is known that in tread rubber for environmentally friendly tires, by using different types of rubber together, opposite performances, such as the balance between rolling resistance and braking performance, and the balance between performance and price, can be improved. For example, Patent Document 2 discloses that a rubber composition using a rubber obtained by blending a high molecular weight hydrogenated conjugated diene rubber with a low molecular weight hydrogenated conjugated diene rubber has high strength, low fuel consumption performance, and excellent processability.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent No. 6004081
[0008] Patent Document 2: Japanese Patent No. 6503064 Summary of the invention
[0009] Problems to be solved by the invention
[0010] As described in Patent Documents 1 and 2, as long as hydrogenated conjugated diene rubber is used to improve wear resistance and is used as a tire, fuel efficiency and wet grip performance are also required performances.
[0011] However, hydrogenation of conjugated diene polymers changes the glass transition temperature of the polymers and tends to make them difficult to be compatible with other polymers. There is a need for conjugated diene polymer compositions that have a high degree of freedom in blending and allow adjustment of the glass transition temperature of the blended materials.
[0012] The present invention aims to solve the above-mentioned problems and to provide a conjugated diene polymer composition which can be used to produce a rubber compound such as a tire tread, which can adjust the glass transition temperature and has a high degree of freedom in compounding, and which has an excellent balance between fuel efficiency and wet grip performance after being vulcanized, and has excellent fracture characteristics, changes in breaking strength after heating, and changes in fracture resistance characteristics when the vulcanization time is extended.
[0013] Means for solving problems
[0014] The present inventors have conducted intensive studies in view of the above-mentioned problems and have found that, for two conjugated diene polymers having different glass transition temperatures, the glass transition temperature of a composition comprising the two conjugated diene polymers can be controlled by designing the structure in such a way that the absolute value of the difference in glass transition temperature, the absolute value of the difference in iodine value and the difference in SP value are within certain ranges, thereby completing the present invention.
[0015] That is, the present invention relates to the following aspects. [1]
[0017] A conjugated diene polymer composition, wherein:
[0018] The conjugated diene polymer composition comprises a conjugated diene polymer (A) and a conjugated diene polymer (B).
[0019] The conjugated diene polymer (A) contains 5% by mass or more and 60% by mass or less of an aromatic vinyl monomer unit, and has an iodine value of 5 to 200 Ig / 100g.
[0020] The conjugated diene polymer (B) contains 0% by mass or more and 50% by mass or less of an aromatic vinyl monomer unit, and has an iodine value of 5 to 200 Ig / 100g.
[0021] From the SP value (MPa) of the conjugated diene polymer (A) 1 / 2 ) minus the SP value (MPa) of the conjugated diene polymer (B) 1 / 2 ) and the difference (SP value of (A) - SP value of (B)) is 0 MPa 1 / 2 Above 0.8MPa 1 / 2 the following,
[0022] The absolute value of the difference in iodine value between the conjugated diene polymer (A) and the conjugated diene polymer (B) (|iodine value of (A) - iodine value of (B)|) is 100 1g / 100g or less,
[0023] The absolute value of the difference in glass transition temperature between the conjugated diene polymer (A) and the conjugated diene polymer (B) (|glass transition temperature of (A) - glass transition temperature of (B)|) is 10° C. to 60° C. [2]
[0025] The conjugated diene polymer composition as described in [1], wherein the conjugated diene polymer (A) has a weight average molecular weight of 230,000 or more and less than 1,000,000. [3]
[0027] The conjugated diene polymer composition as described in [1] or [2], wherein the weight average molecular weight of the conjugated diene polymer (B) is 230,000 or more and less than 1,000,000. [4]
[0029] The conjugated diene polymer composition according to any one of [1] to [3], wherein the mass ratio of the conjugated diene polymer (A) to the conjugated diene polymer (B) (mass of (A) : mass of (B)) is 20:80 to 80:20. [5]
[0031] The conjugated diene polymer composition according to any one of [1] to [4], wherein the modification rate of the conjugated diene polymer (A) and the conjugated diene polymer (B) is 60% or more. [6]
[0033] The conjugated diene polymer composition according to any one of [1] to [5], wherein the absolute value of the difference in iodine value between the conjugated diene polymer (A) and the conjugated diene polymer (B) (|iodine value of (A) - iodine value of (B)|) is less than 80 Ig / 100g. [7]
[0035] A conjugated diene polymer composition as described in any one of [1] to [6], wherein the difference between the content of the aromatic vinyl monomer unit contained in the conjugated diene polymer (A) and the content of the aromatic vinyl monomer unit contained in the conjugated diene polymer (B) (the content of the aromatic vinyl monomer unit contained in (A) - the content of the aromatic vinyl monomer unit contained in (B)) is 5% by mass or more and 30% by mass or less. [8]
[0037] The conjugated diene polymer composition according to any one of [1] to [7], wherein in DSC measurement of the conjugated diene polymer composition, there is only one peak top due to the glass transition of the conjugated diene polymer in the DSC differential curve. [9]
[0039] The conjugated diene polymer composition according to any one of [1] to [8], wherein the glass transition temperature of the conjugated diene polymer composition measured by DSC is -65 to -15°C.
[10]
[0041] A pneumatic tire comprising the conjugated diene polymer composition according to any one of [1] to [9], a plasticizer component, and a filler component.
[11]
[0043] A method for producing a conjugated diene polymer composition, wherein:
[0044] In a conjugated diene polymer comprising a conjugated diene monomer and an aromatic vinyl monomer,
[0045] Investigating changes in glass transition temperature based on the vinyl bond amount and / or the content of the aromatic vinyl monomer, and
[0046] The change in glass transition temperature based on iodine value,
[0047] According to the two changes according to the SP value (MPa 1 / 2 ) is 0MPa 1 / 2 Above 0.8MPa 1 / 2 , and the two conjugated diene polymers (A) and (B) are selected so that the absolute value of the difference in glass transition temperature is 10° C. or more and less than 80° C.,
[0048] The selected conjugated diene polymer (A) and the conjugated diene polymer (B) are mixed to produce a conjugated diene polymer composition.
[0049] Effects of the Invention
[0050] According to the present invention, there is provided a conjugated diene polymer composition which can be used to produce a rubber compound such as a tire tread, the glass transition temperature of which can be adjusted and the degree of freedom of compounding is high, the rubber compound after being made into a vulcanizate has an excellent balance between fuel efficiency and wet grip performance, and has excellent destructive characteristics, changes in breaking strength after heating, and changes in destructive resistance characteristics when the vulcanization time is extended. DETAILED DESCRIPTION
[0051] A specific embodiment of the present invention (hereinafter referred to as “this embodiment”) will be described in detail below.
[0052] It should be noted that the following embodiments are examples for explaining the present invention, and the present invention is not limited to the following embodiments. The present invention can be implemented by appropriately modifying the present invention within the scope of the gist thereof.
[0053] [Conjugated diene polymer composition]
[0054] The conjugated diene polymer composition of the present embodiment includes a conjugated diene polymer (A) and a conjugated diene polymer (B).
[0055] The conjugated diene polymer (A) contains 5% by mass or more and 60% by mass or less of an aromatic vinyl monomer unit, and has an iodine value of 5 to 200 Ig / 100g.
[0056] The conjugated diene polymer (B) contains 0% by mass or more and 50% by mass or less of an aromatic vinyl monomer unit, and has an iodine value of 5 to 200 Ig / 100g.
[0057] From the SP value (MPa) of the conjugated diene polymer (A) 1 / 2 ) minus the SP value (MPa) of the conjugated diene polymer (B) 1 / 2 ) and the difference (SP value of (A) - SP value of (B)) is 0 MPa 1 / 2 Above 0.8MPa 1 / 2 the following,
[0058] The absolute value of the difference in iodine value between the conjugated diene polymer (A) and the conjugated diene polymer (B) (|iodine value of (A) - iodine value of (B)|) is 100 lg / 100g or less,
[0059] The absolute value of the difference in glass transition temperature between the conjugated diene polymer (A) and the conjugated diene polymer (B) (|glass transition temperature of (A) - glass transition temperature of (B)|) is 10° C. to 60° C.
[0060] The conjugated diene polymer composition of the present embodiment has the following effects due to its characteristics: it can produce rubber compounds such as tire treads, the glass transition temperature can be adjusted and the degree of freedom in mixing is high, the rubber compound after being made into a vulcanizate has an excellent balance between fuel efficiency performance and wet grip performance, and has excellent destructive characteristics, changes in breaking strength after heating, and changes in destructive resistance characteristics when the vulcanization time is extended.
[0061] The conjugated diene polymer composition of the present embodiment contains a conjugated diene polymer (A) and a conjugated diene polymer (B).
[0062] The conjugated diene polymer (A) and the conjugated diene polymer (B) used in the present embodiment are preferably random copolymers comprising structural units based on aromatic vinyl monomers (hereinafter also referred to as "aromatic vinyl monomer units"), structural units based on conjugated diene monomers (hereinafter also referred to as "conjugated diene monomer units"), and structural units based on ethylene (hereinafter also referred to as "ethylene units").
[0063] In this specification, "random copolymer" means that the chain consisting of 8 or more consecutive structural units derived from aromatic vinyl compounds is called the long chain ratio, which is 10% by mass or less relative to the total structural units derived from aromatic vinyl compounds. When the long chain ratio is 10% by mass or less, there is a tendency for low fuel consumption to improve.
[0064] Here, the content of the chain consisting of 8 or more consecutive structural units derived from the aromatic vinyl compound is measured using deuterated chloroform as a solvent for the first polymer. 1 In the H-NMR spectrum, the ratio of the integral value of the following range (A) to the total integral value of each chemical shift range (A) to (c) can be used for calculation. For example, when the aromatic vinyl compound is styrene, the ratio of the integral value of the range (A) to the total integral value of each range (A) to (c) can be obtained, and the ratio of styrene can be calculated by multiplying the value by 2.5. This allows the state of the chain of the structural unit derived from the aromatic vinyl compound to be understood.
[0065] (A) Aromatic vinyl compound with 8 or more chains: 6.00≦S<6.68
[0066] (B) Aromatic vinyl compound chains 2 to 7: 6.68≦S<6.89
[0067] (c) Short chain aromatic vinyl compounds: 6.89≦S≦8.00
[0068] The conjugated diene polymer (A) and the conjugated diene polymer (B) used in the present embodiment are random copolymers having structural units based on aromatic vinyl compounds, structural units based on conjugated diene compounds, and structural units based on ethylene. From the perspective of commercial production, it is preferably a hydrogenated copolymer formed by adding hydrogen to a copolymer having an aromatic part as a structural unit based on an aromatic vinyl compound and a conjugated diene part as a structural unit based on a conjugated diene compound, but it can also be a random copolymer formed by copolymerizing an aromatic vinyl compound, a conjugated diene compound, and ethylene. The hydrogenated copolymer is formed by adding hydrogen to the double bond part in the conjugated diene part so that part or all of the conjugated diene part is changed into an ethylene part, and the content of the ethylene part can be increased by increasing the hydrogenation rate.
[0069] It should be noted that in the hydrogenated copolymer, the structure in which hydrogen is added to the form in which a polymer chain is formed at both ends of the main chain of the conjugated diene compound (for example, 1,4-bond of a polymer using 1,3-butadiene as a monomer) is included in the ethylene part, and the structure in which hydrogen is added to other forms (for example, 1,2-bond (vinyl bond) of a polymer using 1,3-butadiene as a monomer) is not included in the ethylene part.
[0070] The aromatic vinyl compound is not particularly limited, and examples thereof include styrene, α-methylstyrene, 1-vinylnaphthalene, 3-vinyltoluene, ethylvinylbenzene, divinylbenzene, 4-cyclohexylstyrene, 2,4,6-trimethylstyrene, etc. These may be used alone or in combination of two or more, and among these, styrene is particularly preferred from the perspective of practicality such as the availability of monomers.
[0071] The conjugated diene compound is not particularly limited, and examples thereof include 1,3-butadiene, isoprene, 1,3-pentadiene, 2,3-dimethylbutadiene, 2-phenyl-1,3-butadiene, 1,3-hexadiene, etc. These substances may be used alone or in combination of two or more. Among these, 1,3-butadiene and isoprene are preferred, and 1,3-butadiene is more preferred, from the perspective of practicality such as the availability of monomers.
[0072] (Conjugated diene polymer (A))
[0073] From the perspective of improving the fracture characteristics and adjusting the glass transition temperature of the compound, the content of the aromatic vinyl monomer unit in the conjugated diene polymer (A) is 5% by mass or more, preferably 10% by mass or more, more preferably 15% by mass or more, and particularly preferably 20% by mass or more. In addition, from the perspective of fuel efficiency, the content of the aromatic vinyl monomer unit in the conjugated diene polymer (A) is 60% by mass or less, preferably 55% by mass or less, more preferably 40% by mass or less, and particularly preferably 45% by mass or less.
[0074] The method for measuring the content of the aromatic vinyl monomer unit is not particularly limited, and the content can be measured by NMR or the like, for example, by the method described in the examples below.
[0075] From the perspective of ease of vulcanization and vulcanization density, the iodine value of the conjugated diene polymer (A) is 51 g / 100 g or more, preferably 71 g / 100 g or more, and more preferably 91 g / 100 g or more. In addition, from the perspective of heat resistance and weather resistance, the iodine value of the conjugated diene polymer (A) is 2001 g / 100 g or less, preferably 1801 g / 100 g or less, more preferably 1501 g / 100 g or less, and particularly preferably 1301 g / 100 g or less.
[0076] The iodine value of the conjugated diene polymer is an indicator of the double bond content of the conjugated diene polymer, and can be controlled by the content of the conjugated diene compound or, when the conjugated diene polymer is obtained by hydrogenation, by the hydrogenation rate.
[0077] In addition, the iodine value of the conjugated diene polymer is calculated by the method described in Examples below.
[0078] The hydrogenation rate (hydrogenation ratio relative to the conjugated diene part) of the conjugated diene polymer (A) is preferably 50 mol% or more, more preferably 60 mol% or more, and further preferably 70 mol% or more from the aspect of crosslinking. In addition, it is preferably 98 mol% or less, more preferably 95 mol% or less, and particularly preferably less than 90 mol% from the aspect of crosslinking.
[0079] It should be noted that the hydrogenation rate of the conjugated diene polymer can be controlled by the amount of hydrogen during the hydrogenation reaction, the reaction time, etc. 1 The spectral reduction rate of the unsaturated bond portion in the spectrum obtained by H-NMR measurement was calculated.
[0080] In the conjugated diene polymer (A), the glass transition temperature is preferably from -85°C to -5°C, more preferably from -75°C to -10°C, and even more preferably from -65°C to -10°C, for example, from the perspective of the fuel efficiency after being made into a tire and the balance between wet grip performance and breaking characteristics.
[0081] The glass transition temperature (Tg) of the conjugated diene polymer is controlled by, for example, the composition ratio of the aromatic vinyl compound to the conjugated diene compound and the iodine value.
[0082] The glass transition temperature of the conjugated diene polymer can be measured by the method described in the examples below.
[0083] From the perspective of compatibility of the conjugated diene polymer, the solubility parameter (hereinafter also referred to as "SP value") of the conjugated diene polymer (A) is preferably 16.8 or more and 18.5 or less. From the perspective of wet grip performance of the tire, the SP value of the conjugated diene polymer (A) is more preferably 17.0 or more, and further preferably 17.1 or more. In addition, from the perspective of fuel efficiency performance of the tire, the SP value of the conjugated diene polymer (A) is more preferably 18.4 or less, further preferably 18.2 or less, and particularly preferably 18.0 or less.
[0084] The solubility parameter (SP value) of the conjugated diene polymer is controlled, for example, by the composition ratio of the aromatic vinyl compound to the conjugated diene compound and the iodine value. There is no particular limitation on the specific method for controlling the SP value, and for example, the SP value can be increased by increasing the composition ratio of the aromatic vinyl compound. In addition, the SP value can be increased by increasing the iodine value.
[0085] The solubility parameter (SP value) of the conjugated diene polymer is calculated by the method described in Examples below.
[0086] It should be noted that the SP value of the conjugated diene polymer was calculated by first calculating the molar volume and cohesive energy of each vinyl polymer using the method of Bicerano (reference: J. Bicerano, Prediction of Polymer Properties, 3rd, Marcel Dekker, 2002). The cohesive energy was calculated using the value calculated by the Van Krevelen method.
[0087] Next, the SP value of the conjugated diene polymer can be determined by the method shown in the calculation formula 17.8 to 17.10 of Jozef. Bicerano: PREDICTION OF POLYMER PROPERTIES, Marcel Dekker, AMERICA (2002), p. 615. It should be noted that crystallinity and microphase separation structures such as block copolymers can be ignored.
[0088] The cohesive energy E (J / mol) / molar volume V (10 -6 m 3 / mol).
[0089] Polystyrene: 36932 / 97.0, 1,2-polybutadiene: 16450 / 58.3, 1,4-polybutadiene: 18579 / 59.1, 1,2-polybutene: 17527 / 65.6, hydrogenated 1,4-polybutadiene: 18146 / 64.4, 1,4-polyisoprene: 22644 / 76.6, 1,2-polyisoprene: 19407 / 75.3, 3,4-polyisoprene: 20908 / 82.2, polyethylene: 9073 / 32.2.
[0090] For example, in the case of a conjugated diene polymer of styrene / 1,4-butadiene having equimolar ratios, the SP value can be calculated as follows.
[0091] E=36932×0.5+18579×0.5=27755(J / mol)
[0092] V=97.0×0.5+59.1×0.5=78.1(m 3 / mol)
[0093] SP value = (27755 / 78.1)1 / 2 = 18.6 ((J / cm 3 ) 1 / 2 )”
[0094] From the perspective of briquetting formability and cold flowability during production, the weight average molecular weight of the conjugated diene polymer (A) is preferably 230,000 or more and less than 1,000,000. In addition, from the perspective of adhesion and destructive properties during production, the weight average molecular weight of the conjugated diene polymer (A) is more preferably 250,000 or more, further preferably 270,000 or more, and particularly preferably 300,000 or more. On the other hand, from the perspective of briquetting formability during production, the weight average molecular weight of the conjugated diene polymer (A) is more preferably 900,000 or less, further preferably 800,000 or less.
[0095] The weight average molecular weight of the conjugated diene polymer can be measured by GPC (gel permeation chromatography) or the like, and can be measured by the method described in the Examples below.
[0096] From the perspective of processability, the molecular weight distribution (Mw / Mn) of the conjugated diene polymer (A) is preferably 1.1 or more, more preferably 1.2 or more, and even more preferably 1.3 or more. From the perspective of low fuel consumption, the molecular weight distribution (Mw / Mn) of the conjugated diene polymer (A) is preferably 3.0 or less, and more preferably 2.5 or less.
[0097] From the viewpoint of facilitating kneading during preparation of a tire compound and preventing cracking of a kneaded product, the Mooney viscosity of the conjugated diene polymer (A) at 100°C is preferably 250 or less, more preferably 200 or less, and even more preferably 180 or less. On the other hand, from the viewpoint of preventing adhesion during production, the Mooney viscosity of the conjugated diene polymer (A) at 100°C is preferably 20 or more, more preferably 30 or more, and even more preferably 40 or more.
[0098] In the present embodiment, the Mooney viscosity is not particularly limited, and can be measured, for example, by a method using an L-shaped rotor in accordance with ISO 289 using a Mooney viscometer.
[0099] (Conjugated diene polymer (B))
[0100] In the conjugated diene polymer (B) used in the present embodiment, the content of the aromatic vinyl monomer unit is 0% by mass or more, preferably 3% by mass or more, more preferably 5% by mass or more, and particularly preferably 8% by mass or more, from the perspective of low temperature characteristics and adjustment of the glass transition temperature of the compound. In addition, in the conjugated diene polymer (B), the content of the aromatic vinyl monomer unit is 50% by mass or less, preferably 40% by mass or less, more preferably 35% by mass or less, and particularly preferably 30% by mass or less, from the perspective of wet grip performance.
[0101] From the aspect of the ease of vulcanization and the vulcanization density, the iodine value of the conjugated diene polymer (B) is 5Ig / 100g or more, preferably 7Ig / 100g or more, and more preferably 9Ig / 100g or more. In addition, from the aspect of heat resistance and weather resistance, the iodine value of the conjugated diene polymer (B) is 200Ig / 100g or less, preferably 180Ig / 100g or less, more preferably 150Ig / 100g or less, and particularly preferably 130Ig / 100g or less. The excellent heat resistance means that, for example, when a tire using a conjugated diene polymer composition or a conjugated diene polymer composition is heated under the atmosphere, the reduction in the destruction characteristics and wet grip performance is small.
[0102] From the aspect of crosslinking, the hydrogenation rate of the conjugated diene polymer (B) (the hydrogenation ratio relative to the conjugated diene portion) is preferably 50 mol% or more, more preferably 60 mol% or more, and further preferably 70 mol% or more. In addition, from the aspect of crosslinking, the hydrogenation rate of the conjugated diene polymer (B) is preferably 98 mol% or less, further preferably 95 mol% or less, and particularly preferably less than 90 mol%.
[0103] From the perspective of fuel efficiency after the tire is manufactured and the balance between wet grip performance and breaking characteristics, the glass transition temperature of the conjugated diene polymer (B) is preferably from -100°C to 15°C, more preferably from -95°C to 20°C, and even more preferably from -95°C to 30°C.
[0104] From the perspective of compatibility of the conjugated diene polymer, the solubility parameter (SP value) of the conjugated diene polymer (B) is preferably 16.4 or more and 18.2 or less. From the perspective of wet grip performance of the tire, the SP value of the conjugated diene polymer (B) is preferably 16.6 or more, more preferably 16.8 or more. In addition, from the perspective of fuel efficiency of the tire, the solubility parameter (SP value) of the conjugated diene polymer (B) is more preferably 18.0 or less, further preferably 17.8 or less, and particularly preferably 17.7 or less.
[0105] From the perspective of the briquetting formability and cold flowability during production, the weight average molecular weight of the conjugated diene polymer (B) is preferably 230,000 or more and less than 1,000,000. In addition, from the perspective of adhesion and destructive properties during production, the weight average molecular weight of the conjugated diene polymer (B) is more preferably 250,000 or more, further preferably 270,000 or more, and particularly preferably 300,000 or more. On the other hand, from the perspective of the briquetting formability during production, the weight average molecular weight of the conjugated diene polymer (B) is more preferably 900,000 or less, further preferably 800,000 or less.
[0106] From the perspective of processability, the molecular weight distribution (Mw / Mn) of the conjugated diene polymer (B) is preferably 1.1 or more, more preferably 1.2 or more, and even more preferably 1.3 or more. From the perspective of low fuel consumption, the molecular weight distribution (Mw / Mn) of the conjugated diene polymer (B) is preferably 3.0 or less, and more preferably 2.5 or less.
[0107] From the viewpoint of facilitating kneading during preparation of a tire compound and preventing cracking of a kneaded product, the Mooney viscosity of the conjugated diene polymer (B) at 100°C is preferably 250 or less, more preferably 200 or less, and even more preferably 180 or less. On the other hand, from the viewpoint of preventing adhesion during production, the Mooney viscosity of the conjugated diene polymer (B) at 100°C is preferably 20 or more, more preferably 30 or more, and even more preferably 40 or more.
[0108] (Glass transition temperature)
[0109] The glass transition temperature of the conjugated diene polymer (A) and the conjugated diene polymer (B) before the hydrogenation reaction can be controlled by, for example, the content of the aromatic vinyl monomer and the amount of 1,2 vinyl bonds.
[0110] The higher the content of aromatic vinyl monomer and the amount of 1,2 vinyl bonds, the higher the glass transition temperature of the conjugated diene polymer. In addition, the glass transition temperature of the conjugated diene polymer can be controlled by hydrogenation rate and iodine value. In the conjugated diene polymer, the higher the hydrogenation rate and the lower the iodine value, the higher the glass transition temperature. However, the glass transition temperature of the conjugated diene polymer before hydrogenation has a great influence.
[0111] (Selection of Conjugated Diene Polymer (A) and Conjugated Diene Polymer (B))
[0112] In this embodiment, in order to obtain a conjugated diene polymer composition in which the difference in SP value, the absolute value of the difference in iodine value and the absolute value of the difference in glass transition temperature are controlled within the above ranges, for example, the following method of selecting the conjugated diene polymer (A) and the conjugated diene polymer (B) can be cited.
[0113] Before selecting the conjugated diene polymer (A) and the conjugated diene polymer (B), it is preferred to first investigate the extent to which the glass transition temperature changes with the vinyl binding amount, the content of the aromatic vinyl monomer and the iodine value. Specifically, (1) the content of the aromatic vinyl monomer is fixed, and the glass transition temperature of the conjugated diene polymers with different vinyl binding amounts and iodine values is measured. It is preferred to measure the content of the aromatic vinyl monomer to more than 3 bases. (2) The vinyl binding amount is fixed, and the glass transition temperature of the polymers with different aromatic vinyl monomer contents and iodine values is measured. It is preferred to measure the vinyl binding amount to more than 3 bases. The above (1) and (2) can be implemented in any order. By preparing these two data, the influence of the vinyl bonding amount, the content of the aromatic vinyl monomer and the iodine value on the glass transition temperature can be understood, and the conjugated diene polymer (A) and the conjugated diene polymer (B) can be selected in such a way that the absolute value of the difference in glass transition temperature (|glass transition temperature of (A) - glass transition temperature of (B)|) is within the above range. The difference in SP value between the conjugated diene polymer (A) and the conjugated diene polymer (B) should also be adjusted, but since the SP value can be calculated as long as the structure is known, there is no obstacle to selection based on the information of the glass transition temperature of the above (1) and (2).
[0114] As a result of investigating the influence of the glass transition temperature, the inventors have found the following tendency. The more the content of the aromatic vinyl monomer and the amount of 1,2 vinyl bonds, the higher the glass transition temperature of the conjugated diene polymer. In addition, the glass transition temperature of the conjugated diene polymer can be controlled, for example, by the hydrogenation rate and the iodine value. In the conjugated diene polymer, the higher the hydrogenation rate, the lower the iodine value. In the hydrogenation reaction of the conjugated diene polymer using a cyclopentadiene titanium catalyst, the 1,2-vinyl bond is preferentially hydrogenated over the 1,4-cis bond and the 1,4-trans bond, and therefore, in the hydrogenation rate region where the 1,2-vinyl bond is hydrogenated, the glass transition temperature is lower than that of the conjugated diene polymer before hydrogenation. In addition, in the conjugated diene polymer, the higher the hydrogenation rate of the 1,4-cis bond and the 1,4-trans bond, the higher the glass transition temperature. However, in the conjugated diene polymer before hydrogenation, the influence of the glass transition temperature is large. The glass transition temperature of a non-hydrogenated polymer (conjugated diene polymer before hydrogenation) depends on the content of the aromatic vinyl monomer and the vinyl bond content, and the content of the aromatic vinyl monomer has a great influence. In a conjugated diene polymer containing an ethylene structure (including a hydrogenated polymer), the vinyl bond content and the iodine value have a great influence, and if the vinyl bond content is low, the glass transition temperature of the conjugated diene polymer after hydrogenation increases significantly.
[0115] From the perspective of improving the uniformity of the vulcanization density after the sulfide is prepared, thereby improving the destructive characteristics and reducing the extent of the deterioration of the physical properties after the vulcanization time is extended, the absolute value of the difference between the iodine value of the conjugated diene polymer (A) and the iodine value of the conjugated diene polymer (B) (|iodine value of (A) - iodine value of (B)|) is 100 Ig / 100 g or less, preferably 90 Ig / 100 g or less, more preferably 80 Ig / 100 g or less, and further preferably less than 80 Ig / 100 g. The lower limit of the absolute value of the difference between the iodine value of the conjugated diene polymer (A) and the iodine value of the conjugated diene polymer (B) (|iodine value of (A) - iodine value of (B)|) is not particularly limited, and is, for example, 0 Ig / 100 g or more.
[0116] From the viewpoints of compatibility, fuel efficiency, and wear resistance, the difference obtained by subtracting the SP value of the conjugated diene polymer (B) from the SP value of the conjugated diene polymer (A) (SP value of (A) - SP value of (B)) is 0.80 MPa. 1 / 2 Below, preferably 0.70MPa 1 / 2 Below, more preferably 0.65MPa 1 / 2 Below, more preferably 0.60MPa 1 / 2 Below, particularly preferably 0.50 MPa 1 / 2The lower limit of the difference obtained by subtracting the SP value of the conjugated diene polymer (B) from the SP value of the conjugated diene polymer (A) (SP value of (A) - SP value of (B)) is 0 MPa 1 / 2 above.
[0117] From the perspective of the degree of freedom of blending when preparing a tire compound, and the balance between fuel efficiency and wet grip performance, the absolute value of the difference between the glass transition temperature of the conjugated diene polymer (A) and the glass transition temperature of the conjugated diene polymer (B) (|glass transition temperature of (A) - glass transition temperature of (B)|) is 10°C or more, preferably 15°C or more, and more preferably 20°C or more. In addition, from the perspective of rubber compatibility, the absolute value of the difference between the glass transition temperature of the conjugated diene polymer (A) and the glass transition temperature of the conjugated diene polymer (B) (|glass transition temperature of (A) - glass transition temperature of (B)|) is 60°C or less, preferably 50°C or less, and more preferably 45°C or less.
[0118] (Glass transition temperature of conjugated diene polymer composition)
[0119] The glass transition temperature of the conjugated diene polymer composition of the present embodiment is preferably 1. The case where the glass transition temperature is 1 is determined by the fact that in the DSC measurement of the conjugated diene polymer composition, the peak top based on the glass transition from the conjugated diene polymer in the DSC differential curve is 1 (one inflection point). For a broad peak, if there is one inflection point, the glass transition temperature is also 1; the case where there are shoulder peaks such as two or more inflection points is not included in the mode where the glass transition temperature is 1. Preferably, the conjugated diene polymer (A) is compatible with the conjugated diene polymer (B). In addition, from the aspect of wet grip performance, the glass transition temperature of the conjugated diene polymer composition of the present embodiment is preferably above -65°C, more preferably above -60°C, and further preferably above -55°C. In addition, from the aspect of fuel consumption performance and low temperature characteristics, the glass transition temperature of the conjugated diene polymer composition of the present embodiment is preferably below -10°C, more preferably below -13°C, and further preferably below -15°C.
[0120] When the conjugated diene polymer (A) and the conjugated diene polymer (B) are compatible, it is easy to control the glass transition temperature of the conjugated diene polymer composition of the present embodiment, which is preferred from this perspective; in addition, the interface between the conjugated diene polymer (A) and the conjugated diene polymer (B) is reduced, and the fuel consumption performance is excellent, which is therefore preferred.
[0121] (Ratio of the conjugated diene polymer (A) to the conjugated diene polymer (B))
[0122] The conjugated diene polymer composition of the present embodiment comprises a conjugated diene polymer (A) and a conjugated diene polymer (B). From the perspective of the hardness of the mixed compound and the control of the glass transition temperature of the composition, the mass ratio (mass of (A): mass of (B)) is preferably 20:80 to 80:20, more preferably 25:75 to 75:25, and further preferably 30:70 to 70:30. The glass transition temperature of the conjugated diene polymer composition of the present embodiment is controlled by changing the glass transition temperature of the polymer itself according to the polymer structure of the conjugated diene polymer (A) and the conjugated diene polymer (B), and can also be controlled to a certain extent by the mixing ratio. Whether the glass transition temperature of the conjugated diene polymer composition of the present embodiment is controlled by the polymer structure or by the ratio depends on the physical property balance required by the mixed compound. From the perspective of being able to use products of the same structure to verify multiple mixing conditions and being effective, it is preferably controlled by changing the ratio of polymers determined by the structure.
[0123] When the conjugated diene polymer composition of the present embodiment is used for a tire, the hardness is generally adjusted to about 60 to 70. It is preferred that the blending ratio be set in consideration of the hardness during mixing in addition to the SP value difference and glass transition temperature between the conjugated diene polymer (A) and the conjugated diene polymer (B).
[0124] (Difference in content of aromatic vinyl monomer units)
[0125] In the conjugated diene polymer composition of the present embodiment, the difference between the content of the aromatic vinyl monomer unit contained in the conjugated diene polymer (A) and the content of the aromatic vinyl monomer unit contained in the conjugated diene polymer (B) (the content of the aromatic vinyl monomer unit contained in (A) - the content of the aromatic vinyl monomer unit contained in (B)) is preferably 5% by mass or more and 30% by mass or less, more preferably 8% by mass or more and 30% by mass or less, and more preferably 10% by mass or more and 28% by mass or less. In the conjugated diene polymer composition of the present embodiment, when the difference between the content of the aromatic vinyl monomer unit contained in the conjugated diene polymer (A) and the content of the aromatic vinyl monomer unit contained in the conjugated diene polymer (B) is within the above range, there is a tendency to have an excellent balance between fuel efficiency performance and handling stability.
[0126] (Method for producing conjugated diene polymer)
[0127] (Polymerization method)
[0128] Regarding the polymerization method of the conjugated diene polymer used in the present embodiment, there is no particular restriction as long as the above-mentioned specific physical properties can be obtained, and any of solution polymerization, gas phase polymerization, and bulk polymerization can be used. From the perspective of commercial production, solution polymerization is particularly preferred. In addition, the polymerization form can be any of intermittent and continuous.
[0129] When the solution polymerization method is used, the monomer concentration in the solution is preferably 5% by mass or more, more preferably 10% by mass or more. When the monomer concentration in the solution is 5% by mass or more, the amount of the conjugated diene polymer obtained is sufficient and the cost tends to be reduced. In addition, the monomer concentration in the solution is preferably 50% by mass or less, more preferably 30% by mass or less. When the monomer concentration in the solution is 50% by mass or less, the solution viscosity is reduced, it is easy to stir, and there is a tendency for polymerization to become easy.
[0130] (Polymerization initiator)
[0131] In the case of anionic polymerization, there is no particular limitation on the polymerization initiator, but an organic lithium compound is preferably used. As the organic lithium compound, a substance having an alkyl group having 2 to 20 carbon atoms is preferred, and examples thereof include ethyl lithium, n-propyl lithium, isopropyl lithium, n-butyl lithium, sec-butyl lithium, tert-butyl lithium, tert-octyl lithium, n-decyl lithium, phenyl lithium, 2-naphthyl lithium, 2-butyl-phenyl lithium, 4-phenyl-butyl lithium, cyclohexyl lithium, cyclopentyl lithium, the reaction product of diisopropenylbenzene and butyl lithium, etc. Among these, n-butyl lithium or sec-butyl lithium is preferred from the aspects of availability and safety.
[0132] When coordination polymerization is performed, it is preferable to use a polymerization catalyst composition described in JP-A-2020-45500 as a polymerization initiator.
[0133] (Aggregation method)
[0134] There is no particular limitation on the method of producing a conjugated diene polymer by anionic polymerization or coordination polymerization using a polymerization initiator, and a conventionally known method can be used. Specifically, in an organic solvent inert to the reaction, such as a hydrocarbon solvent such as an aliphatic, alicyclic, or aromatic hydrocarbon compound, butyl lithium is used as a polymerization initiator, and styrene, 1,3-butadiene, ethylene, etc. are polymerized in the presence of a randomizer as required, thereby obtaining the target conjugated diene polymer.
[0135] (Hydrocarbon solvents)
[0136] As the hydrocarbon solvent, a hydrocarbon solvent having 3 to 8 carbon atoms is preferred, and examples thereof include propane, n-butane, isobutane, n-pentane, isopentane, n-hexane, cyclohexane, propylene, 1-butene, isobutylene, trans-2-butene, cis-2-butene, 1-pentene, 2-pentene, 1-hexene, 2-hexene, benzene, toluene, xylene, ethylbenzene, etc. These substances may be used alone or in combination of two or more.
[0137] (Randomizer in anionic polymerization)
[0138] The randomizer refers to a compound that has the effect of controlling the microstructure of the conjugated diene part in the conjugated diene polymer (for example, the increase of 1,2-bonding in butadiene, 3,4-bonding in isoprene, etc.), or controlling the composition distribution of the monomer units in the copolymer (for example, the randomization of styrene units and butadiene units in styrene butadiene copolymers). There is no particular limitation on the randomizer, and any substance can be selected from the known compounds commonly used as randomizers. For example, dimethoxybenzene, tetrahydrofuran, dimethoxyethane, diethylene glycol dibutyl ether, diethylene glycol dimethyl ether, 2,2-bis(2-tetrahydrofuranyl)propane, triethylamine, pyridine, N-methylmorpholine, N,N,N',N'-tetramethylethylenediamine, 1,2-dipiperidylethane and other ethers and tertiary amines can be cited. In addition, potassium salts such as potassium tert-amylate and potassium tert-butoxide, and sodium salts such as sodium tert-amylate can also be used. These randomizers can be used alone or in combination of two or more. In addition, the amount of the randomizer is preferably 0.01 molar equivalent or more, more preferably 0.05 molar equivalent or more per 1 mole of the organic lithium compound. When the amount of the randomizer is less than 0.01 molar equivalent, the addition effect is small, and there is a tendency that randomization is not easy. In addition, the amount of the randomizer is preferably 1000 molar equivalent or less, more preferably 500 molar equivalent or less per 1 mole of the organic lithium compound. When the amount of the randomizer exceeds 1000 molar equivalents, the reaction rate of the monomer changes significantly, and there is a tendency that randomization becomes difficult.
[0139] (Reaction temperature)
[0140] The reaction temperature during polymerization is not particularly limited as long as the reaction proceeds appropriately, but is usually preferably -10°C to 100°C, more preferably 25°C to 70°C.
[0141] (Modification process)
[0142] By reacting the active end of the conjugated diene polymer obtained by the polymerization process with a compound having a functional group that interacts with silicon oxide, a functional group that interacts with silicon oxide can be introduced into the polymerization termination end of the conjugated diene polymer. Thus, a conjugated diene polymer with a modified polymerization termination end can be obtained. It should be noted that in this specification, the end refers to the part other than the structure of the monomer having a carbon-carbon double bond that exists at the end of the molecular chain. When the polymerization termination end is coupled, the termination end in the obtained conjugated diene polymer undergoes star-shaped branching and is no longer the so-called terminal side. Here, the process is described on the premise that it is the termination terminal side in the polymerization process.
[0143] The conjugated diene polymer used in the modification reaction (hereinafter also referred to as the terminal modification reaction) can be unmodified or modified as long as it has an active terminal. In addition, as a compound having a functional group introduced into the polymerization termination terminal of the conjugated diene polymer, as long as it is a compound having a functional group that interacts with silicon oxide and can react with the polymerization active terminal, there is no particular limitation. As the method for this introduction, it is preferably a method for introducing using a terminal modifier containing a tin atom or a nitrogen atom, and more preferably a method for introducing using a terminal modifier containing a nitrogen atom. The method for determining the modification rate described later is a method when the modification is nitrogen-modified, but in the case of tin modification, it is only necessary to adopt a modification rate determination method suitable for tin modification.
[0144] As the terminal modifier containing a nitrogen atom, isocyanate compounds, isothiocyanate compounds, isocyanuric acid derivatives, nitrogen-containing carbonyl compounds, nitrogen-containing vinyl compounds, nitrogen-containing epoxides, nitrogen-containing alkoxysilane compounds, etc. are preferred from the aspects of polymerization productivity and high modification rate.
[0145] As these terminal modifiers containing nitrogen atoms, nitrogen group-containing alkoxysilane compounds are more preferred from the viewpoints of polymerization productivity, high modification rate, and tensile strength after the tire is produced.
[0146] Preferred examples of nitrogen-containing alkoxysilane compounds include 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silacyclopentane, 2,2-diethoxy-1-(3-triethoxysilylpropyl)-1-aza-2-silacyclopentane, 2,2-dimethoxy-1-(4-trimethoxysilylbutyl)-1-aza-2-silacyclohexane, 2,2-dimethoxy-1-(5-trimethoxysilylpentyl)-1-aza-2-silacycloheptane, and 2,2-dimethoxy-1-(4-trimethoxysilylbutyl)-1-aza-2-silacyclohexane. Methoxy-1-(3-dimethoxymethylsilylpropyl)-1-aza-2-silacyclopentane, 2,2-diethoxy-1-(3-diethoxyethylsilylpropyl)-1-aza-2-silacyclopentane, 2-methoxy-2-methyl-1-(3-trimethoxysilylpropyl)-1-aza-2-silacyclopentane, 2-ethoxy-2-ethyl-1-(3-triethoxysilylpropyl)-1-aza-2-silacyclopentane, 2-methoxy-2-methyl-1-(3-dimethoxymethylsilylpropyl)-1-aza-2-silacyclopentane )-1-aza-2-silacyclopentane, and 2-ethoxy-2-ethyl-1-(3-diethoxyethylsilylpropyl)-1-aza-2-silacyclopentane, tris(3-trimethoxysilylpropyl)amine, tris(3-methyldimethoxysilylpropyl)amine, tris(3-triethoxysilylpropyl)amine, tris(3-methyldiethoxysilylpropyl)amine, tris(trimethoxysilylmethyl)amine, tris(2-trimethoxysilylethyl)amine, and tris(4-trimethoxysilylbutyl)amine, tetra[3- [2,2-dimethoxy-1-aza-2-silacyclopentane)propyl]-1,3-propylenediamine, tetrakis(3-trimethoxysilylpropyl)-1,3-propylenediamine, tetrakis(3-trimethoxysilylpropyl)-1,3-bisaminomethylcyclohexane, and N1-(3-(bis(3-(trimethoxysilyl)propyl)amino)propyl)-N1-methyl-N3-(3-(methyl(3-(trimethoxysilyl)propyl)amino)propyl)-N3-(3-(trimethoxysilyl)propyl)-1,3-propylenediamine.
[0147] The terminal modification reaction can be carried out, for example, in the form of a solution reaction. The solution reaction can be carried out using a solution containing unreacted monomers after the polymerization reaction in the polymerization step is terminated, or the copolymer contained in the solution can be separated and dissolved in a suitable solvent such as cyclohexane. In addition, the terminal modification reaction can be carried out using any of intermittent and continuous methods. At this time, the method for adding the terminal modifier is not particularly limited, and a method of adding uniformly, a method of adding in batches, a method of adding continuously, etc. can be cited.
[0148] The amount of the compound used in the terminal modification reaction can be appropriately set according to the type of compound used in the reaction, and is preferably 0.1 molar equivalent or more, more preferably 0.3 molar equivalent or more relative to the metal atom participating in the polymerization reaction possessed by the polymerization initiator. By making the amount of the compound used in the terminal modification reaction 0.1 molar equivalent or more, the modification reaction can be fully carried out, and the dispersibility of silicon oxide can be appropriately improved.
[0149] The temperature of the terminal modification reaction is usually the same as the temperature of the above-mentioned polymerization reaction, preferably -20 to 150° C., more preferably 0 to 120° C., and particularly preferably 20 to 100° C. If the modification reaction temperature is low, the viscosity of the modified copolymer tends to increase.
[0150] On the other hand, if the temperature of the modification reaction is high, the polymerization active terminal is easily deactivated. The reaction time of the modification reaction is preferably 1 minute to 5 hours, more preferably 2 minutes to 1 hour.
[0151] (Modification rate of conjugated diene polymer composition)
[0152] From the viewpoint of fuel efficiency, the modification rate of the conjugated diene polymer composition of the present embodiment is preferably 40% or more, more preferably 50% or more, and even more preferably 60% or more.
[0153] In addition, from the perspective of suppressing the uneven distribution of fillers such as silica in the compound, the modification rate of the conjugated diene polymer (A) is preferably 40% or more, more preferably 50% or more, and further preferably 60% or more. The upper limit of the modification rate of the conjugated diene polymer (A) is not particularly limited, but from the perspective of the processability of the compound, it is, for example, 99% or less.
[0154] In addition, from the perspective of suppressing the uneven distribution of fillers such as silicon oxide in the compound, the modification rate of the conjugated diene polymer (B) is preferably 40% or more, more preferably 50% or more, and further preferably 60% or more. The upper limit of the modification rate of the conjugated diene polymer (B) is not particularly limited, and from the perspective of the processability of the compound, it is, for example, 99% or less.
[0155] From the perspective of improving fuel efficiency and stability of the performance of the blend, the modification rates of the conjugated diene polymer (A) and the conjugated diene polymer (B) contained in the conjugated diene polymer composition of the present embodiment are preferably both 40% or more, more preferably 50% or more, further preferably 60% or more, and particularly preferably 65% or more.
[0156] (Reaction termination)
[0157] Anionic polymerization can be terminated by adding a reaction terminator commonly used in the field. Such a reaction terminator is not particularly limited, and for example, a polar solvent having an active proton such as alcohol such as methanol, ethanol, isopropanol or acetic acid and a mixed solution thereof or a mixed solution of these polar solvents with a non-polar solvent such as hexane or cyclohexane can be cited. Regarding the addition amount of the reaction terminator, it is sufficient to be the same molar amount or twice the molar amount relative to the anionic polymerization initiator.
[0158] (Hydrogenation method)
[0159] In the case of manufacturing the conjugated diene polymer used in the present embodiment by hydrogenation, there is no particular limitation on the method and reaction conditions of hydrogenation as long as the above-mentioned specific physical properties can be obtained, and hydrogenation can be carried out by known methods and known conditions. The hydrogenation is usually carried out in the presence of a hydrogenation catalyst at 20 to 150° C. and 0.1 to 10 MPa of hydrogen pressure. It should be noted that the hydrogenation rate can be arbitrarily selected by changing the amount of the hydrogenation catalyst, the hydrogen pressure during the hydrogenation reaction, the reaction time, etc.
[0160] As a hydrogenation catalyst, a compound containing any element of the metals of Groups 4 to 11 of the periodic table can generally be used. Specifically, compounds containing atoms of Ti, V, Co, Ni, Zr, Ru, Rh, Pd, Hf, Re, and Pt can be used as hydrogenation catalysts, but are not limited thereto. As more specific hydrogenation catalysts, there are no particular limitations, and examples thereof include metallocene compounds of Ti, Zr, Hf, Co, Ni, Pd, Pt, Ru, Rh, and Re; supported heterogeneous catalysts formed by loading metals such as Pd, Ni, Pt, Rh, and Ru on carriers such as carbon, silicon oxide, aluminum oxide, and diatomaceous earth; homogeneous Ziegler-type catalysts formed by combining organic salts or acetylacetonates of metal elements such as Ni and Co with reducing agents such as organic aluminum; organic metal compounds or complexes of Ru, Rh, and the like; fullerenes and carbon nanotubes containing hydrogen, and the like.
[0161] Among these, from the aspect that the hydrogenation reaction can be carried out in a homogeneous phase in an inert organic solvent, a metallocene compound containing any one of Ti, Zr, Hf, Co, and Ni is preferred. A metallocene compound containing any one of Ti, Zr, and Hf is more preferred. The hydrogenation catalyst can be used alone or in combination of two or more.
[0162] The preferred method for obtaining the conjugated diene polymer is the following method: solution polymerization is carried out, the obtained polymer solution is directly used for modification treatment, and then a hydrogenation step is applied as needed. The conjugated diene polymer is obtained, for example, by removing the solvent from the polymer solution obtained above and separating the polymer. In order to separate the polymer, it can be carried out by, but not limited to, a drying operation such as a known desolvation method such as steam stripping and a heat treatment using a dehydrating extruder, a drying extruder, or a conveyor.
[0163] (Method for producing conjugated diene polymer composition)
[0164] About the method for obtaining the conjugated diene polymer composition of the present embodiment, as long as the above-mentioned characteristics can be obtained, there is no particular limitation, for example, conjugated diene polymer (A) and conjugated diene polymer (B) and the composition mixed as required can be enumerated by using open mixers (such as rollers), closed mixers (such as Banbury mixers) and other mixers to mix and obtain the method for the composition. In addition, the polymer solution of conjugated diene polymer (A) and conjugated diene polymer (B) can be mutually blended (mixed), and then known desolventizing method and drying operation are carried out for the conjugated diene polymer composition, thus obtaining the composition. In the method, in the case of obtaining a conjugated diene polymer composition, by making conjugated diene polymer (A) and conjugated diene polymer (B) appropriately compatible, the conjugated diene polymer composition is appropriately foamed when leaving the drying extruder, thus increasing the specific surface area, therefore compared with a single conjugated diene polymer (B), drying rate tends to improve, and it is preferred in terms of productivity.
[0165] In particular, the method for producing the conjugated diene polymer composition of the present embodiment is preferably the following method:
[0166] In a conjugated diene polymer comprising a conjugated diene monomer and an aromatic vinyl monomer,
[0167] Investigating changes in glass transition temperature based on the vinyl bond amount and / or the content of the aromatic vinyl monomer, and
[0168] The change in glass transition temperature based on iodine value,
[0169] According to the two changes according to the SP value (MPa 1 / 2 ) is 0MPa 1 / 2 Above 0.8MPa 1 / 2 , and the two conjugated diene polymers (A) and (B) are selected so that the absolute value of the difference in glass transition temperature is 10° C. or more and less than 80° C.,
[0170] The selected conjugated diene polymer (A) and the conjugated diene polymer (B) are mixed to obtain a conjugated diene polymer composition.
[0171] Specific methods for selecting the conjugated diene polymer (A) and the conjugated diene polymer (B) include the methods for selecting the conjugated diene polymer (A) and the conjugated diene polymer (B) described above.
[0172] (Pneumatic tire)
[0173] The pneumatic tire of the present embodiment contains the above-mentioned conjugated diene polymer composition, a plasticizer component, and a filler component.
[0174] The pneumatic tire of the present embodiment can be produced using a rubber composition described later.
[0175] [Rubber composition]
[0176] The rubber composition used in the pneumatic tire of the present embodiment includes the above-mentioned conjugated diene polymer as a rubber component. In addition to the above-mentioned conjugated diene polymer, a rubber component commonly used in common tire rubber compounds can also be used. Such a rubber component is not particularly limited, and examples thereof include natural rubber (NR), isoprene rubber (IR), styrene-butadiene rubber (SBR), butadiene rubber (BR), etc. These can be used alone or in combination of two or more.
[0177] The filler component is mixed into the rubber compound for the purpose of reinforcing the rubber. Specific examples of the filler component are not particularly limited, and examples thereof include white fillers (inorganic fillers) such as silicon oxide, calcium carbonate, mica, aluminum hydroxide, magnesium oxide, magnesium hydroxide, clay, talc, aluminum oxide, titanium oxide, mica, and carbon black. These components may be used alone or in combination of two or more. Silicon oxide and carbon black are preferred, and their combination is more preferred.
[0178] The silicon oxide is not particularly limited, and examples thereof include dry-process silicon oxide (anhydrous silicon oxide) and wet-process silicon oxide (hydrous silicon oxide). Wet-process silicon oxide is preferred because it contains a large number of silanol groups.
[0179] The nitrogen adsorption specific surface area (N2SA) of silicon oxide is preferably 60 m2 from the perspective of wear resistance. 2 / g or more, more preferably 120m 2 / g or more, preferably 300m / g from the perspective of low fuel consumption 2 / g or less, more preferably 200m 2 / g or less.
[0180] It should be noted that the nitrogen adsorption specific surface area of silicon oxide is a value measured by the BET method in accordance with ASTM D3037-81.
[0181] The content of silica is preferably 30 parts by mass or more, more preferably 50 parts by mass or more, based on 100 parts by mass of the rubber component from the viewpoint of low fuel consumption, and is preferably 120 parts by mass or less, more preferably 100 parts by mass or less from the viewpoint of Mooney viscosity.
[0182] The carbon black is not particularly limited, and examples thereof include furnace blacks such as SAF, ISAF, HAF, MAF, FEF, SRF, GPF, APF, FF, CF, SCF, and ECF; acetylene black; thermal blacks such as FT and MT; channel blacks such as EPC, MPC, and CC; graphite, etc. These materials may be used alone or in combination of two or more.
[0183] The nitrogen adsorption specific surface area (N2SA) of carbon black is usually 5 to 200 m 2 / g, preferably 50m / g from the perspective of wear resistance 2 / g or more, more preferably 80m 2 / g or more, and preferably 150m / g from the perspective of low fuel consumption 2 / g or less, more preferably 120m 2 / g or less. In addition, the dibutyl phthalate (DBP) absorption of carbon black is generally 5 to 300 mL / 100 g, preferably with a lower limit of 80 mL / 100 g and an upper limit of 180 mL / 100 g. The nitrogen adsorption specific surface area is measured in accordance with ASTM D4820-93, and the DBP absorption value is measured in accordance with ASTM D2414-93.
[0184] Regarding the carbon black content, from the perspective of wear resistance, it is preferably 1 part by mass or more, more preferably 3 parts by mass or more, relative to 100 parts by mass of the rubber component, and from the perspective of low fuel consumption, it is preferably 30 parts by mass or less, more preferably 15 parts by mass or less, relative to 100 parts by mass of the rubber component.
[0185] Silicon oxide is preferably used in combination with a silane coupling agent. As the silane coupling agent, a conventionally known substance can be used. Specific examples of the silane coupling agent are not particularly limited, and examples thereof include bis(3-triethoxysilylpropyl)tetrasulfide, bis(2-triethoxysilylethyl)tetrasulfide, bis(3-trimethoxysilylpropyl)tetrasulfide, bis(2-trimethoxysilylethyl)tetrasulfide, bis(3-triethoxysilylpropyl)trisulfide, bis(3-trimethoxysilylpropyl)trisulfide, bis(3-triethoxysilylethyl)tetrasulfide, Sulfide-based compounds include bis(3-trimethoxysilylpropyl) disulfide, bis(3-trimethoxysilylpropyl) disulfide, 3-trimethoxysilylpropyl-N,N-dimethylthiocarbamoyl tetrasulfide, 3-trimethoxysilylpropylbenzothiazolyl tetrasulfide, 3-triethoxysilylpropylbenzothiazolyl tetrasulfide, 3-triethoxysilylpropylmethacrylate monosulfide, and 3-trimethoxysilylpropylmethacrylate monosulfide. , 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 2-mercaptoethyltrimethoxysilane, 2-mercaptoethyltriethoxysilane and other mercapto-based, vinyltriethoxysilane, vinyltrimethoxysilane and other vinyl-based, 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-(2-aminoethyl)aminopropyltriethoxysilane, 3-(2-aminoethyl)aminopropyltrimethoxysilane and other amino-based, γ -glycidoxypropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, γ-glycidoxypropylmethyldimethoxysilane and other glycidoxy series, 3-nitropropyltrimethoxysilane, 3-nitropropyltriethoxysilane and other nitro series, 3-chloropropyltrimethoxysilane, 3-chloropropyltriethoxysilane, 2-chloroethyltrimethoxysilane, 2-chloroethyltriethoxysilane and other chlorine series. It should be noted that the above-mentioned silane coupling agent can be used alone or in combination of two or more. Among them, from the perspective of coupling effect, processability and cost of the silane coupling agent, sulfide-based silane coupling agents are preferred, and bis(3-triethoxysilylpropyl)tetrasulfide and bis(3-triethoxysilylpropyl)disulfide are more preferred.
[0186] The content of the silane coupling agent is preferably 3 parts by mass or more, more preferably 5 parts by mass or more, relative to 100 parts by mass of silicon oxide from the perspective of low fuel consumption and wear resistance, and is preferably 15 parts by mass or less, more preferably 10 parts by mass or less, relative to 100 parts by mass of silicon oxide from the perspective of Mooney viscosity.
[0187] The plasticizer component is not particularly limited, and examples thereof include oil, resin, antioxidant, wax, stearic acid, vulcanization accelerator, etc. These components may be used alone or in combination of two or more.
[0188] There is no particular limitation on the oil, and examples thereof include aromatic mineral oils (viscosity-gravity constant (VGC value) 0.900 to 1.049), cycloparaffin mineral oils (VGC value 0.850 to 0.899), and paraffin mineral oils (VGC value 0.790 to 0.849). The polycyclic aromatic content of the extender oil is preferably less than 3% by mass, more preferably less than 1% by mass. The polycyclic aromatic content is measured according to the British Petroleum Institute 346 / 92 method. In addition, the aromatic compound content (CA) of the extender oil is preferably 20% by mass or more. Two or more of these extender oils may also be used in combination.
[0189] Regarding the oil content, from the perspective of Mooney viscosity, it is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, relative to 100 parts by mass of the rubber component, and from the perspective of low fuel consumption, it is preferably 50 parts by mass or less, more preferably 40 parts by mass or less, relative to 100 parts by mass of the rubber component.
[0190] The resin is not particularly limited, and examples thereof include C5-based petroleum resins, C9-based petroleum resins, coumarone indene resins, indene resins, phenolic resins, copolymers of α-methylstyrene and / or styrene, etc. These components may be used alone or in combination of two or more. Among them, coumarone indene resins, phenolic resins (particularly terpene phenol resins), copolymers of α-methylstyrene and / or styrene are preferred, and copolymers of α-methylstyrene and styrene are more preferred.
[0191] Regarding the resin content, from the perspective of wet grip performance, it is preferably 1 part by mass or more, more preferably 3 parts by mass or more, relative to 100 parts by mass of the rubber component, and from the perspective of low fuel consumption, it is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, relative to 100 parts by mass of the rubber component.
[0192] The anti-aging agent is not particularly limited, and examples thereof include naphthylamine anti-aging agents such as phenyl-α-naphthylamine; diphenylamine anti-aging agents such as octylated diphenylamine and 4,4'-bis(α,α'-dimethylbenzyl)diphenylamine; p-phenylenediamine anti-aging agents such as N-phenyl-N'-isopropyl-p-phenylenediamine, N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine and N,N'-di-2-naphthyl-p-phenylenediamine; quinoline anti-aging agents such as polymers of 2,2,4-trimethyl-1,2-dihydroquinoline; monophenol anti-aging agents such as 2,6-di-tert-butyl-4-methylphenol and styrenated phenol; bisphenol, triphenol, and polyphenol anti-aging agents such as tetrakis-[methylene-3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate]methane, etc. These components may be used alone or in combination of two or more. Among them, p-phenylenediamine-based antioxidants are preferred, and N-phenyl-N′-isopropyl p-phenylenediamine is more preferred. The content of the antioxidant is preferably 0.1 to 5 parts by mass, more preferably 0.2 to 4 parts by mass, based on 100 parts by mass of the rubber component.
[0193] The wax is not particularly limited, and examples thereof include petroleum waxes such as paraffin wax and microcrystalline wax; natural waxes such as plant wax and animal wax; synthetic waxes such as polymers such as ethylene and propylene. These components may be used alone or in combination of two or more. Petroleum waxes are preferred, and paraffin wax is more preferred. The content of the wax is preferably 0.1 to 5 parts by mass, and more preferably 0.2 to 4 parts by mass, relative to 100 parts by mass of the rubber component.
[0194] As stearic acid, a known substance can be used, and products of, for example, NOF Corporation, Kao Corporation, Wako Pure Chemical Industries, Ltd., Chiba Fatty Acid Co., Ltd., etc. can be used but not limited thereto. These components can be used alone or in combination of two or more. The content of stearic acid is preferably 0.1 to 5 parts by mass, more preferably 0.2 to 4 parts by mass, relative to 100 parts by mass of the rubber component.
[0195] The vulcanization accelerator is not particularly limited, and examples thereof include thiazole-based vulcanization accelerators such as 2-mercaptobenzothiazole, dibenzothiazolyl disulfide, and N-cyclohexyl-2-benzothiazolyl sulfenamide; thiuram-based vulcanization accelerators such as tetramethylthiuram monosulfide and tetramethylthiuram disulfide; sulfenamide-based vulcanization accelerators such as N-cyclohexyl-2-benzothiazole sulfenamide, N-tert-butyl-2-benzothiazole sulfenamide, N-oxyethylene-2-benzothiazole sulfenamide, N-oxyethylene-2-benzothiazole sulfenamide, and N,N'-diisopropyl-2-benzothiazole sulfenamide; and guanidine-based vulcanization accelerators such as diphenylguanidine, di-o-tolylguanidine, and o-tolylbiguanide. These components may be used alone or in combination of two or more. Among them, for the reason of more suitably obtaining the effect of the present invention, sulfenamide-based vulcanization accelerators are preferred, and N-cyclohexyl-2-benzothiazolesulfenamide is more preferred. In addition, it is also preferred to further use a guanidine-based vulcanization accelerator. The content of the vulcanization accelerator is preferably 0.1 to 5 parts by mass, and more preferably 0.2 to 4 parts by mass, relative to 100 parts by mass of the rubber component.
[0196] The rubber composition may contain, in addition to the above components, vulcanizing agents such as sulfur, vulcanization activators such as zinc oxide, organic peroxides, processing aids such as lubricants, and anti-aging agents, which are compounding agents conventionally used in the rubber industry.
[0197] The vulcanizing agent is not particularly limited, and sulfur can be preferably used. The sulfur content is preferably 0.5 to 5 parts by mass, more preferably 1 to 3 parts by mass, based on 100 parts by mass of the rubber component. This can more preferably achieve the effects of the present invention.
[0198] The rubber composition is produced by a common method, that is, by kneading the above-mentioned components using a Banbury mixer, a kneader, an open roll mill, etc., and then vulcanizing the mixture.
[0199] The rubber composition can be used in various parts of a tire (tread, bead, tire carcass, belt, bead, clinch, chafer, etc.), and can be preferably used as a tread. In the case of a tread of a two-layer structure, it is composed of a surface layer (tread crown) and an inner layer (tread base).
[0200] The tread of the multi-layer structure can be produced by a method of laminating a sheet into a predetermined shape, loading the sheet into two or more extruders, and forming the sheet into two or more layers at the die outlet of the extruder.
[0201] The pneumatic tire of the present embodiment is manufactured by a common method using the above-mentioned rubber composition. That is, the rubber component and the above-mentioned various compounding agents are mixed as necessary, and the obtained rubber composition is extruded in accordance with the shape of each tire component such as the tread at an unvulcanized stage, and molded on a tire molding machine together with other tire components by a common method to form an unvulcanized tire. The unvulcanized tire is heated and pressurized in a vulcanizer to obtain the pneumatic tire of the present embodiment.
[0202] The pneumatic tire of the present embodiment can be suitably used as a tire for a passenger car, a tire for a truck or a bus, a tire for a two-wheeled vehicle, a tire for a racing car, and the like, and can be suitably used as a tire for a passenger car in particular.
[0203] Example
[0204] The present embodiment will be described in more detail below with reference to specific examples and comparative examples, but the present embodiment is not limited to the following examples and comparative examples.
[0205] Various physical properties in Examples and Comparative Examples were measured by the methods shown below.
[0206] (Weight average molecular weight (Mw) of conjugated diene polymer)
[0207] The chromatogram was measured using a gel permeation chromatography (hereinafter also referred to as "GPC") measuring apparatus having three columns connected and using polystyrene gel as a filler, and the weight average molecular weight (Mw) of the conjugated diene polymer was determined based on a calibration curve obtained using standard polystyrene.
[0208] Tetrahydrofuran (hereinafter also referred to as "THF") added with 5 mmol / L triethylamine was used as the eluent. As the column, a guard column: a trade name "TSKguardcolumn SuperH-H" manufactured by Tosoh Corporation, and a column: a trade name "TSKgel SuperH5000", "TSKgel SuperH6000", and "TSKgel SuperH7000" manufactured by Tosoh Corporation were used.
[0209] A differential refractive index (hereinafter also referred to as "RI") detector (trade name "HLC8020" manufactured by Tosoh Corporation) was used under the conditions of an oven temperature of 40°C and a THF flow rate of 0.6 mL / min. 10 mg of a sample for measurement was dissolved in 20 mL of THF to prepare a measurement solution, and 20 μL of the measurement solution was injected into the GPC measurement device for measurement.
[0210] (Modification rate of conjugated diene polymer)
[0211] The modification rate of the conjugated diene polymer was measured by column adsorption GPC method as follows: The modification rate was measured by utilizing the property that the conjugated diene polymer modified with a nitrogen atom-containing functional group is adsorbed on the column.
[0212] For a sample solution containing a conjugated diene polymer and a low molecular weight internal standard polystyrene, the amount of adsorption on the silica column is measured from the difference between the chromatogram measured by the polystyrene column and the chromatogram measured by the silica column to determine the modification rate of the conjugated diene polymer.
[0213] Specifically, it is as follows.
[0214] Preparation of sample solution:
[0215] 10 mg of a conjugated diene polymer and 5 mg of standard polystyrene were dissolved in 20 mL of THF to prepare a sample solution.
[0216] GPC measurement conditions using a column filled with polystyrene gel:
[0217] The chromatogram was measured as follows using a GPC measuring apparatus to which three columns using polystyrene-based gel as a filler were connected.
[0218] THF with 5 mmol / L triethylamine added was used as the eluent, and 20 μL of the sample solution was injected into the GPC measuring device for measurement. For the column, a guard column: a trade name "TSKguardcolumn SuperH-H" manufactured by Tosoh Corporation, and a column: a trade name "TSKgel SuperH5000", "TSKgel SuperH6000", and "TSKgelSuperH7000" manufactured by Tosoh Corporation were used. The chromatogram was obtained by measuring with an RI detector (HLC8020 manufactured by Tosoh Corporation) at a temperature of 40°C in the chromatographic column thermostat and a THF flow rate of 0.6 mL / min.
[0219] GPC measurement conditions using silica column:
[0220] A product name "HLC-8320GPC" manufactured by Tosoh Corporation was used, THF was used as the eluent, 50 μL of the sample solution was injected into the GPC measuring device, and a chromatogram was obtained using an RI detector under the conditions of a chromatographic column thermostat temperature of 40°C and a THF flow rate of 0.5 ml / min. As for the column, the product names "Zorbax PSM-1000S", "PSM-300S", and "PSM-60S" were connected and used, and the product name "DIOL4.6×12.5mm 5micron" was connected as a guard column in the front section for use.
[0221] Calculation method of modification rate:
[0222] Assuming that the total peak area of the chromatogram obtained using a polystyrene column is 100, the peak area of the sample is P1, and the peak area of the standard polystyrene is P2, the total peak area of the chromatogram using a silica column is 100, and the peak area of the sample is P3, and the peak area of the standard polystyrene is P4, the modification rate (%) is calculated by the following formula.
[0223] Modification rate (%) = [1-(P2×P3) / (P1×P4)]×100
[0224] (where P1+P2=P3+P4=100)
[0225] (Glass transition temperature of conjugated diene polymer and conjugated diene polymer composition, and peak top due to glass transition of conjugated diene polymer in differential scanning calorimetry (hereinafter also referred to as “DSC”) differential curve)
[0226] A conjugated diene polymer or a conjugated diene polymer composition is used as a sample, and a DSC curve is recorded while heating in a predetermined temperature range in accordance with ISO 22768:2006. The peak top (inflection point) of the DSC differential curve is taken as the glass transition temperature, and the number of peak tops is counted.
[0227] In the case of a conjugated diene polymer composition, when there are two or more peak tops in the DSC differential curve, two or more values are described.
[0228] (Bound styrene content of conjugated diene polymer (content of aromatic vinyl monomer unit (mass %)), 1,2-vinyl bond content (content of 1,2-vinyl bond in butadiene unit (mol % in butadiene)), vinyl structure content (mass %))
[0229] Using conjugated diene polymers as 1 The sample subjected to H-NMR measurement was measured for the amount of bound styrene, the amount of 1,2-vinyl binding, and the amount of ethylene structure. The measurement conditions were as follows.
[0230] (Measurement conditions)
[0231] Measuring equipment: JNM-LA400 (manufactured by JEOL)
[0232] Solvent: deuterated chloroform
[0233] Measurement sample: Conjugated diene polymer
[0234] Sample concentration: 50 mg / mL
[0235] Observation frequency: 400MHz
[0236] Chemical shift standard: TMS (tetramethylsilane)
[0237] Pulse delay: 2.904 seconds
[0238] Scan times: 64 times
[0239] Pulse width: 45°
[0240] Measurement temperature: 26℃
[0241] (Styrene block content of conjugated diene polymer)
[0242] The styrene block content of the conjugated diene polymer is measured as follows.
[0243] A chain consisting of eight or more styrene structural units is defined as a styrene block, and its content is determined as follows: For a conjugated diene polymer, the styrene block is determined by measuring the styrene block at 400 MHz using deuterated chloroform as a solvent. 1 The ratio of the integrated values of each chemical shift range of the following (X) was determined from the H-NMR spectrum to determine the content of the styrene block contained in the conjugated diene polymer.
[0244] (X) Aromatic vinyl compound with 8 or more chains: 6.00≦S<6.68
[0245] (Iodine value of conjugated diene polymer)
[0246] The iodine value of the conjugated diene polymer was calculated according to the method described in "JIS K 0070:1992".
[0247] (SP value of conjugated diene polymer)
[0248] The molar volume and cohesive energy of the conjugated diene polymer were calculated by the method of Bicerano (reference: J. Bicerano, Prediction of Polymer Properties, 3rd, Marcel Dekker, 2002). The bound styrene content, 1,2-vinyl binding content, and ethylene structure content measured by the above method, as well as the butene content, 1,4-cis binding content, and 1,4-trans binding content calculated from these parameters were used.
[0249] As for the cohesive energy, a value calculated according to the Van Krevelen method was used.
[0250] Next, the SP value of the conjugated diene copolymer was determined by the method shown in the calculation formula 17.8 to 17.10 of Jozef. Bicerano: PREDICTION OF POLYMER PROPERTIES, Marcel Dekker, AMERICA (2002), p. 615. It should be noted that crystallinity and microphase separation structures of block copolymers are not taken into consideration.
[0251] (Manufacture of hydrogenation catalyst)
[0252] In the Examples and Comparative Examples described below, the hydrogenation catalyst used in the preparation of the conjugated diene polymer was prepared by the following method.
[0253] Into a nitrogen-purged reaction vessel, 1 liter of dried and purified cyclohexane was added, 100 mmol of bis(η5-cyclopentadienyl)titanium dichloride was added, and while stirring thoroughly, a n-hexane solution containing 200 mmol of trimethylaluminum was added, and the mixture was reacted at room temperature for about 3 days to obtain a hydrogenation catalyst (TC-1).
[0254] (Polymerization Example 1) Conjugated Diene Polymer S1
[0255] A temperature-controllable autoclave having an internal volume of 40 L and equipped with a stirrer and a jacket was used as a reactor. 2,100 g of initial 1,3-butadiene from which impurities had been removed in advance, 780 g of styrene, 21,000 g of cyclohexane, 30 mmol of tetrahydrofuran (THF) as a polar substance, and 15.5 mmol of 2,2-bis(2-tetrahydrofuryl)propane (BOP) were added to the reactor, and the internal temperature of the reactor was maintained at 42°C.
[0256] 22.1 mmol of n-butyllithium as a polymerization initiator was supplied to the above reactor.
[0257] After the polymerization reaction started, the temperature in the reactor began to rise due to the heat generated by the polymerization. After the monomer conversion rate in the reactor reached 99%, 120 g of 1,3-butadiene was added to carry out the reaction.
[0258] The temperature in the reactor finally reached 76°C. Two minutes after reaching the peak of the reaction temperature, 4.4 mmol of 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silacyclopentane (Compound 1) was added to the reactor as a coupling agent, and a coupling reaction was carried out for 20 minutes. 4.4 mmol of methanol was added to the polymer solution as a reaction terminator to obtain a conjugated diene polymer solution before hydrogenation.
[0259] To the obtained conjugated diene polymer solution, 12.6 g of n-octadecyl 3-(3,5-di-tert-butyl-4-hydrogenated hydroxyphenyl)-propionate (antioxidant 1) and 3.0 g of 4,6-bis(octylthiomethyl)-o-cresol (antioxidant 2) were added as antioxidants, followed by desolventization and drying to obtain a conjugated diene polymer (S1).
[0260] The conjugated diene polymer (S1) was analyzed by the above method. The analysis results are shown in Table 3.
[0261] (Polymerization Example 2) Conjugated Diene Polymer S2
[0262] A temperature-controllable autoclave having an internal volume of 40 L and equipped with a stirrer and a jacket was used as a reactor. 2,100 g of initial 1,3-butadiene from which impurities had been removed in advance, 780 g of styrene, 21,000 g of cyclohexane, 30 mmol of tetrahydrofuran (THF) as a polar substance, and 15.5 mmol of 2,2-bis(2-tetrahydrofuryl)propane were added to the reactor, and the internal temperature of the reactor was maintained at 42°C.
[0263] 22.1 mmol of n-butyllithium as a polymerization initiator was supplied to the above reactor.
[0264] After the polymerization reaction started, the temperature in the reactor began to rise due to the heat generated by the polymerization. After the monomer conversion rate in the reactor reached 99%, 120 g of 1,3-butadiene was added to carry out the reaction.
[0265] The temperature in the reactor finally reached 76°C. Two minutes after reaching the peak of the reaction temperature, 4.4 mmol of 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silacyclopentane (Compound 1) was added to the reactor as a coupling agent, and a coupling reaction was carried out for 20 minutes. 4.4 mmol of methanol was added to the polymer solution as a reaction terminator to obtain a conjugated diene polymer solution before hydrogenation.
[0266] The above-mentioned hydrogenation catalyst (TC-1) is added to the conjugated diene polymer solution in an amount of 90 ppm based on titanium per 100 parts by mass of the conjugated diene polymer, and a hydrogenation reaction is carried out under the conditions of a hydrogen pressure of 0.85 MPa and an average temperature of 90°C until a specific hydrogen reaction is completed. Thereafter, 12.6 g of n-octadecyl-3-(3,5-di-tert-butyl-4-hydrogenated hydroxyphenyl)-propionate (antioxidant 1) and 3.0 g of 4,6-bis(octylthiomethyl)-o-cresol (antioxidant 2) as antioxidants are added to the conjugated diene polymer solution, and then desolventization and drying treatment are carried out to obtain a conjugated diene polymer S2.
[0267] The conjugated diene polymer S2 was analyzed by the above method. The analysis results are shown in Table 3.
[0268] (Polymerization Examples 4 and 7) Conjugated Diene Polymers T1 and U1
[0269] Conjugated diene polymers T1 and U1 were obtained in the same manner as in Polymerization Example 1 except that the polymerization formula was changed to that described in Table 1. In Polymerization Examples 4 and 7, 3-(4-methylpiperazin-1-yl)propyltriethoxysilane (Compound 2) was used as a coupling agent.
[0270] The conjugated diene polymers T1 and U1 were analyzed by the above method. The analysis results are shown in Table 3.
[0271] (Polymerization Examples 3, 5, 6, 8 and 9) Conjugated diene polymers S3, T2, T3, U2 and U3
[0272] Except for changing the polymerization formula described in Table 1, the same method as in Polymerization Example 2 was carried out to obtain conjugated diene polymers S3, T2, T3, U2 and U3.
[0273] The conjugated diene polymers S3, T2, T3, U2 and U3 were analyzed by the above method. The analysis results are shown in Table 3.
[0274] (Polymerization Examples 10, 14, 17 and 20) Conjugated Diene Polymers V1, W1, X1 and Y1
[0275] Conjugated diene polymers V1, W1, X1 and Y1 were obtained in the same manner as in Polymerization Example 1 except that the polymerization formula was changed to that shown in Table 2. In Polymerization Example 14, silicon tetrachloride (Compound 3) was used as a coupling agent.
[0276] The conjugated diene polymers V1, W1, X1, and Y1 were analyzed by the above method.
[0277] (Polymerization Examples 11, 12, 13, 15, 16, 18, 19 and 21) Conjugated diene polymers V2, V3, V4, W2, W3, X2, X3 and Y2
[0278] Conjugated diene polymers V2, V3, V4, W2, W3, X2, X3 and Y2 were obtained in the same manner as in Polymerization Example 2 except that the polymerization formula was changed to the one shown in Table 2.
[0279] The conjugated diene polymers V2, V3, V4, W2, W3, X2, X3 and Y2 were analyzed by the above method.
[0280]
[0281]
[0282] Compound 1, Compound 2, and Compound 3 in Tables 1 and 2 are shown below.
[0283] Compound 1: 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silacyclopentane
[0284] Compound 2: 3-(4-methylpiperazin-1-yl)propyltriethoxysilane
[0285] Compound 3: Silicon tetrachloride
[0286]
[0287]
[0288] [Examples 1 to 20 and Comparative Examples 1 to 11]
[0289] The conjugated diene polymers obtained in the polymerization examples 1 to 21 shown in Tables 1 and 2 were blended (mixed) in the proportions shown in Tables 5 and 6 to prepare conjugated diene polymer compositions. It should be noted that in Examples 1 to 20, for the conjugated diene polymers, the changes in the glass transition temperature based on the 1,2-vinyl bond amount and the bonded styrene amount (content of the aromatic vinyl monomer) shown in Tables 3 and 4 and the changes in the glass transition temperature based on the iodine value were investigated, and the SP value (MPa) was calculated based on the two changes. 1 / 2 ) is 0MPa 1 / 2 Above 0.8MPa 1 / 2 The two conjugated diene polymers (A) and (B) are selected so that the absolute value of the difference in glass transition temperature is 10° C. or more and less than 80° C. The physical properties of the obtained conjugated diene polymer composition are measured by the above methods.
[0290] Tables 5 and 6 show the blending (mixing) ratio of the conjugated diene polymer composition and the physical properties of the conjugated diene polymer composition.
[0291]
[0292]
[0293] [Examples 21 to 40 and Comparative Examples 12 to 22]
[0294] Using the conjugated diene polymer compositions prepared in Examples 1 to 20 and Comparative Examples 1 to 11 as raw material rubbers, rubber compounds containing the raw material rubbers were obtained according to the mixing conditions and kneading methods shown below. The various properties of the obtained rubber compounds were measured according to the following methods. The measurement results are shown in Tables 7 and 8.
[0295] (Matching conditions)
[0296] Raw rubber (conjugated diene polymer compositions of Examples 1 to 20 and Comparative Examples 1 to 11): 100 parts by mass
[0297] The amount of each compounding agent added below is expressed in parts by mass relative to 100 parts by mass of the rubber component (conjugated diene polymer composition) not including the rubber softener.
[0298] Silicon oxide 1 (trade name "Ultrasil 7000GR" manufactured by Evonik Degussa, nitrogen adsorption specific surface area 170 m 2 / g): 50.0 parts by mass
[0299] Silicon oxide 2 (trade name "Zeosil Premium 200MP" manufactured by Rhodia, nitrogen adsorption specific surface area 220 m 2 / g): 25.0 parts by mass
[0300] Carbon black (trade name "SEAST KH (N339)" manufactured by Tokai Tanso Co., Ltd.): 5.0 parts by mass
[0301] Silane coupling agent (trade name "Si75" manufactured by Evonik Degussa, bis(triethoxysilylpropyl) disulfide): 6.0 parts by mass
[0302] SRAE oil (trade name "Process NC140" manufactured by JX Nippon Oil & Energy Corporation): 25.0 parts by mass
[0303] Zinc white: 2.5 parts by mass
[0304] Stearic acid: 1.0 parts by mass
[0305] Anti-aging agent (N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine): 2.0 parts by mass
[0306] Sulfur: 2.2 parts by mass
[0307] Vulcanization accelerator 1 (N-cyclohexyl-2-benzothiazolylsulfenamide): 1.7 parts by mass
[0308] Vulcanization accelerator 2 (diphenylguanidine): 2.0 parts by mass
[0309] Total: 222.4 parts by mass
[0310] (Mixing method)
[0311] The above materials were kneaded by the following method to obtain a rubber compound. A closed mixer (content 0.3 L) equipped with a temperature control device was used as the first stage of kneading. The raw rubber components (conjugated diene polymer compositions of Examples 1 to 20 and Comparative Examples 1 to 11), fillers (silicon oxide 1, silicon oxide 2, carbon black), silane coupling agents, SRAE oil, zinc white and stearic acid were kneaded under the conditions of a filling rate of 65% and a rotor speed of 30 to 50 rpm. At this time, the temperature of the closed mixer was controlled to obtain each compound at a discharge temperature of 155 to 160°C.
[0312] Next, as the second stage of mixing, the above-obtained mixture is cooled to room temperature, an anti-aging agent is added, and mixing is performed again to improve the dispersion of silicon oxide. In this case, the discharge temperature of the mixture is also adjusted to 155-160°C by temperature control of the mixer. After cooling, as the third stage of mixing, sulfur and vulcanization accelerators 1 and 2 are added and mixed using an open mill set at 70°C to obtain a rubber mixture. Thereafter, the obtained rubber mixture is molded and vulcanized at 160°C for 20 minutes using a vulcanization press. The various properties of the vulcanized rubber mixture (Examples 21-40, Comparative Examples 12-22) are evaluated. Specifically, the evaluation is performed by the following method.
[0313] <Evaluation items and test methods>
[0314] The obtained vulcanized rubber compound was subjected to the following evaluations. The results are shown in Tables 7 and 8 below.
[0315] (Fuel efficiency, wet grip performance)
[0316] The viscoelastic parameters of the vulcanized rubber compound were measured in torsional vibration mode using a viscoelasticity tester "ARES" manufactured by Rheometric Scientific.
[0317] Tan δ measured at 50°C, 10 Hz frequency, and 3% strain is used as an index of fuel efficiency. A larger index indicates better fuel efficiency.
[0318] In addition, tan δ measured at 0°C, a frequency of 10 Hz, and a strain of 1% is used as an index of wet grip performance. A larger index indicates better wet grip performance.
[0319] The fuel efficiency and wet grip performance of the vulcanized rubber compounds of Examples 21 to 25 and Comparative Examples 13 and 14 were indexed by setting the results of the fuel efficiency and wet grip performance of the vulcanized rubber compound of Comparative Example 12 to 100, as shown in Table 7. The fuel efficiency and wet grip performance of the vulcanized rubber compounds of Examples 26 to 28 and Comparative Example 16 were indexed by setting the results of the fuel efficiency and wet grip performance of the vulcanized rubber compound of Comparative Example 15 to 100, as shown in Table 7. The fuel efficiency and wet grip performance of the vulcanized rubber compounds of Examples 29 to 32 were indexed by setting the results of the fuel efficiency and wet grip performance of the vulcanized rubber compound of Comparative Example 17 to 100, as shown in Table 8. The fuel efficiency and wet grip performance of the vulcanized rubber compounds of Examples 33 to 35 and Comparative Example 19 were indexed by setting the results of the fuel efficiency and wet grip performance of the vulcanized rubber compound of Comparative Example 18 to 100, as shown in Table 8. The fuel efficiency and wet grip performance of the vulcanized rubber compounds of Examples 36 and 37 were indexed by setting the results of the fuel efficiency and wet grip performance of the vulcanized rubber compound of Comparative Example 20 to 100, as shown in Table 8. The fuel efficiency and wet grip performance of the vulcanized rubber compound of Example 38 were indexed by setting the results of the fuel efficiency and wet grip performance of the vulcanized rubber compound of Comparative Example 21 to 100, as shown in Table 8. The fuel efficiency performance and wet grip performance of the vulcanized rubber compounds of Examples 39 and 40 were indexed as shown in Table 8, with the results of the fuel efficiency performance and wet grip performance of the vulcanized rubber compound of Comparative Example 22 being set to 100.
[0320] (Destructive characteristics)
[0321] The breaking strength and breaking elongation of the vulcanized rubber compound were measured according to the tensile test method of JIS K6251, and the product of the measured values was used as the destructive property.
[0322] Regarding the fracture characteristics, the results of the vulcanized rubber compounds of Examples 21 to 25 and Comparative Examples 13 and 14 were indexed by setting the result of the vulcanized rubber compound of Comparative Example 12 to 100, as shown in Table 7. The results of the vulcanized rubber compounds of Examples 26 to 28 and Comparative Example 16 were indexed by setting the result of the vulcanized rubber compound of Comparative Example 15 to 100, as shown in Table 7. The results of the vulcanized rubber compounds of Examples 29 to 32 were indexed by setting the result of the vulcanized rubber compound of Comparative Example 17 to 100, as shown in Table 8. The results of the vulcanized rubber compounds of Examples 33 to 35 and Comparative Example 19 were indexed by setting the result of the vulcanized rubber compound of Comparative Example 18 to 100, as shown in Table 8. The results of the vulcanized rubber compounds of Examples 36 and 37 were indexed by setting the result of the vulcanized rubber compound of Comparative Example 20 to 100, as shown in Table 8. The results of the vulcanized rubber compound of Example 38 were indexed by setting the result of the vulcanized rubber compound of Comparative Example 21 to 100, as shown in Table 8. The results of the vulcanized rubber compounds of Examples 39 and 40 were indexed by setting the result of the vulcanized rubber compound of Comparative Example 22 to 100, as shown in Table 8.
[0323] (Change in breaking strength after heating)
[0324] In addition, the vulcanized rubber compound was heated at 150°C for 5 hours in the atmosphere, and then the breaking strength was measured by the same method as above, and the change in breaking strength before and after heating was calculated. The evaluation was performed as follows: the smaller the change, the better the heat resistance, indicating more sustainable production.
[0325] In Tables 7 and 8, the change in breaking strength before and after heating was recorded as ◎ when it was 0 MPa or more and less than 1.0 MPa, ○ when it was 1.0 MPa or more and less than 2.5 MPa, △ when it was 2.5 MPa or more and less than 4.0 MPa, and × when it was 4.0 MPa or more, and the change in breaking strength after heating was evaluated. In practical terms, △, ○, and ◎ are required, and ○ and ◎ are preferred.
[0326] (Changes in damage resistance as the curing time increases)
[0327] When a vulcanized rubber compound was obtained by the same method as above, only the vulcanization time was changed, and vulcanization was performed at 160° C. for 40 minutes using a vulcanization press.
[0328] The rubber compound vulcanized under the above conditions was subjected to the same measurement of fracture characteristics as above, and the difference in fracture characteristics from the rubber compound vulcanized at 160° C. for 20 minutes was evaluated.
[0329] In Tables 7 and 8, based on the destructive properties of the rubber compound vulcanized at 160°C for 20 minutes, the case where the destructive properties of the rubber compound vulcanized at 160°C for 40 minutes deteriorated by 20% or more was marked as ×, the case where the deterioration was 10% or more and less than 20% was marked as △, the case where the deterioration was 4% or more and less than 10% was marked as 0, the case where the deterioration was less than 4% or there was no deterioration (equivalent) or the case where it was optimized was marked as ◎.
[0330] When the vulcanization time is extended, the smaller the deterioration of the breaking properties is, the more stable the physical properties of the rubber compound are. In practical terms, it is necessary to be △, 0, or ◎, and preferably 0 or ◎.
[0331]
[0332] As shown in Tables 7 and 8, it was confirmed that the rubber compounds (Examples 21 to 40) using the conjugated diene polymer compositions obtained in Examples 1 to 20 had an excellent balance between fuel efficiency and wet grip performance after being vulcanized, and were excellent in breaking properties, change in breaking strength after heating, and change in breaking resistance when the vulcanization time was extended, compared to the rubber compounds (Comparative Examples 12 to 22) using the conjugated diene polymer compositions obtained in Comparative Examples 1 to 11. It was also confirmed that a conjugated diene polymer composition having a high degree of freedom in compounding was obtained by this Example.
[0333] Industrial Applicability
[0334] The conjugated diene polymer composition of the present invention has industrial applicability as materials for tire treads, automobile interior and exterior products, anti-vibration rubber, belts, shoes, foams, and various industrial products.
Claims
1. A conjugated diene polymer composition, wherein: The conjugated diene polymer composition comprises a conjugated diene polymer A and a conjugated diene polymer B in a mass ratio of 20:80 to 80:
20. The conjugated diene polymer A contains 5 mass % or more and 60 mass % or less of an aromatic vinyl monomer unit, and has an iodine value of 5 Ig / 100 g to 200 Ig / 100 g. The conjugated diene polymer B contains 0 mass % or more and 50 mass % or less of an aromatic vinyl monomer unit, and has an iodine value of 5 Ig / 100 g to 200 Ig / 100 g. The difference obtained by subtracting the SP value of the conjugated diene polymer B from the solubility parameter SP value of the conjugated diene polymer A, that is, the SP value of A minus the SP value of B, is 0 MPa. 1 / 2 Above 0.8MPa 1 / 2 the following, The absolute value of the difference between the iodine values of the conjugated diene polymer A and the conjugated diene polymer B, namely, |iodine value of A - iodine value of B| is 100 Ig / 100 g or less, The absolute value of the difference in glass transition temperature between the conjugated diene polymer A and the conjugated diene polymer B, ie, |glass transition temperature of A−glass transition temperature of B| is 10° C. or more and 60° C. or less.
2. The conjugated diene polymer composition according to claim 1, wherein The weight average molecular weight of the conjugated diene polymer A is 230,000 or more and less than 1,000,000.
3. The conjugated diene polymer composition according to claim 1 or 2, wherein The weight average molecular weight of the conjugated diene polymer B is 230,000 or more and less than 1,000,000.
4. The conjugated diene polymer composition according to claim 1 or 2, wherein The modification rates of the conjugated diene polymer A and the conjugated diene polymer B are 60% or more.
5. The conjugated diene polymer composition according to claim 1 or 2, wherein The absolute value of the difference between the iodine values of the conjugated diene polymer A and the conjugated diene polymer B, ie, |iodine value of A−iodine value of B| is less than 80 Ig / 100g.
6. The conjugated diene polymer composition according to claim 1 or 2, wherein The difference between the content of the aromatic vinyl monomer unit contained in the conjugated diene polymer A and the content of the aromatic vinyl monomer unit contained in the conjugated diene polymer B, i.e., the content of the aromatic vinyl monomer unit contained in A minus the content of the aromatic vinyl monomer unit contained in B, is 5% by mass or more and 30% by mass or less.
7. The conjugated diene polymer composition according to claim 1 or 2, wherein In the DSC measurement of the conjugated diene polymer composition, there is one peak top due to the glass transition of the conjugated diene polymer in the DSC differential curve.
8. The conjugated diene polymer composition according to claim 1 or 2, wherein The glass transition temperature of the conjugated diene polymer composition measured by DSC is -65°C to -15°C.
9. The conjugated diene polymer composition according to claim 1 or 2, wherein The conjugated diene polymer A contains 20% by mass or more and 55% by mass or less of an aromatic vinyl monomer unit.
10. The conjugated diene polymer composition according to claim 1 or 2, wherein: The conjugated diene polymer B contains 0% by mass to 35% by mass of aromatic vinyl monomer units.
11. The conjugated diene polymer composition according to claim 1 or 2, wherein The absolute value of the difference in glass transition temperature between the conjugated diene polymer A and the conjugated diene polymer B, ie, |glass transition temperature of A−glass transition temperature of B|, is 45° C. or less.
12. The conjugated diene polymer composition according to claim 1 or 2, wherein: The iodine value of the conjugated diene polymer A is not less than 9 1g / 100g and not more than 180 1g / 100g.
13. The conjugated diene polymer composition according to claim 1 or 2, wherein: The iodine value of the conjugated diene polymer B is not less than 9 1g / 100g and not more than 180 1g / 100g.
14. The conjugated diene polymer composition according to claim 1 or 2, wherein The conjugated diene polymer A has a glass transition temperature of -85°C or higher and -5°C or lower.
15. The conjugated diene polymer composition according to claim 1 or 2, wherein The conjugated diene polymer B has a glass transition temperature of -100°C to -15°C.
16. The conjugated diene polymer composition according to claim 1 or 2, wherein: The SP value of the conjugated diene polymer A is 16.8 MPa 1 / 2 Above 18.5MPa 1 / 2 the following.
17. The conjugated diene polymer composition according to claim 1 or 2, wherein: The SP value of the conjugated diene polymer B is 16.4 MPa 1 / 2 Above 18.2MPa 1 / 2 the following.
18. The conjugated diene polymer composition according to claim 8, wherein The conjugated diene polymer composition has a glass transition temperature of -55°C to -15°C as measured by DSC. 19 . A pneumatic tire comprising the conjugated diene polymer composition according to claim 1 , a plasticizer component, and a filler component.
20. A method for producing a conjugated diene polymer composition, wherein: In a conjugated diene polymer comprising a conjugated diene monomer and an aromatic vinyl monomer, investigating changes in glass transition temperature based on the vinyl bond amount and / or the content of the aromatic vinyl monomer, and The change in glass transition temperature based on iodine value, According to the two changes, the absolute value of the difference in iodine value is less than 100Ig / 100g, and the difference in SP value is 0MPa 1 / 2 Above 0.8MPa 1 / 2 The two conjugated diene polymers are selected in such a manner that the absolute value of the difference in glass transition temperature is 10° C. or more and less than 80° C.: a conjugated diene polymer A containing 5% by mass or more and 60% by mass or less of an aromatic vinyl monomer unit and having an iodine value of 5 Ig / 100 g to 200 Ig / 100 g; and a conjugated diene polymer B containing 0% by mass or more and 50% by mass or less of an aromatic vinyl monomer unit and having an iodine value of 5 Ig / 100 g to 200 Ig / 100 g. The selected conjugated diene polymer A and the conjugated diene polymer B are mixed at a mass ratio of 20:80 to 80:20 to produce a conjugated diene polymer composition.
21. The method for producing a conjugated diene polymer composition according to claim 20, wherein: The conjugated diene polymer A and the conjugated diene polymer B are respectively the conjugated diene polymer A and the conjugated diene polymer B in the conjugated diene polymer composition according to any one of claims 2 to 18.
Citation Information
Patent Citations
Thermal color printer
JP1985004081A
Multi-component copolymer, rubber composition and tire
JP2020045500A
Rubber composition and tire
JP2017214493A
Process for the preparation of halogen-carrying rubberlike copolymers
US3936430A